Growth-specific Expression and Influencing Factors of Hdh-MLGF in Pacific Abalone, Haliotis Discus Hannai - Hanif Md Abu; Doo-Hyun Cho; Yusin Cho; Won-Kyo Lee; Kang Hee Kho (한국해양생명과학회지, 2025)
Growth is a fundamental and vital characteristic of abalone, regulated by both cell number and size, and modulated by growth-related genes. The mollusk-like growth factor (MLGF) is a secreted protein that plays a key role in the growth and development of Pacific abalone. In this study, the growth-specific expression of Hdh-MLGF were analyzed under different conditions commonly encountered by Pacific abalone in aquaculture systems. The expression of Hdh-MLGF varied significantly with growth patterns, showed higher expression in rapid-growing individuals and lower expression in slow-growing abalone. Under starvation conditions, Hdh-MLGF expression was downregulated as the duration of starvation progressed. Under thermal stress, Hdh-MLGF expression increased during the first 12 hours at 25 ℃ stress. However, at 30 ℃, the highest expression was recorded after 6 hours of thermal stress. These results provide valuable insights for future research on this growth factor in abalone and its aquaculture management.